Human Resource Requirement Under the Context of Universal Health Coverage (UHC) in Bangladesh: Current Situation and Future Challenges - Talukder, Md Humayun Kabir; Rahman, Md Mahfuzar; Nuruzzaman, Md (Anwer Khan Modern Medical College Journal, 2017)
"Human resources" have been described as "the heart of the health system in any country". The fact of health worker shortage in Bangladesh is well documented and regarded as one of the major challenges of the country's health system as mentioned in the national health policy 2011 and also in the strategic plan for health, population and nutrition sector development programme (HPNSDP 2011-2016). Universal Health Coverage (UHC) has got immense attention around the world. This is true that Bangladesh has been able to achieve remarkable progresses on the overall health status. However, considering the growing needs of the health system and rapid transition in the disease pattern (e.g. from communica ble to non communicable), long way to go towards a responsive, competent and equity based health system. Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 34-39